PENERAPAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Nur Rohmah Wibawati (Jurnal Ilmiah Pendidikan TRISALA, 2021)
Graduate Competency Standards which are the reference for school level learning are made according to the times. The selection of learning methods must be in accordance with learning that will support the improvement of the quality of graduation standards. STEM is one of the appropriate methods used today that puts forward the creativity of students in overcoming problems from the point of view of knowledge, technology, design and mathematical calculations of students. The STEM method involves students in their ability to think theoretically, techniques using appropriate technology, the ability to design a product, and also the ability to calculate both in terms of costs and estimation of the material requirements used to produce a product. These abilities will be maximized through the STEM method so that it can support graduate competency standards. Thus the competence of graduate students at each level will be used in overcoming the problems that occur today. The STEM method will be applied in learning Islamic Religious Education as a subject that involves practical values ​​in each sub-learning. With STEM, Islamic Religious Education materials will be able to be applied to the daily lives of students in the current era.